Cascade palladium-catalyzed direct intramolecular arylation/alkene isomerization sequences: synthesis of indoles and benzofurans. - Yagoubi, M; Cruz, A; Nichols, P; Elliott, R; Willis, M (2010)
One route, two cycles: A palladium-catalyzed intramolecular direct arylation reaction combined with an isomerization step provided a straightforward synthetic route to both indoles and benzofurans (see scheme). Isolation and functionalization of intermediate alkene isomers allowed the formation of variants having substituents remote from the core. © 2010 WILEY-VCH Verlag GmbH and Co. KGaA, Weinheim.